Natural Insecticide Spray for Aedes sp., Made from Ethanol Extract of Purple Eggplant Fruit (Solanum melongena L.) (Medico Legal Update, 2019)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the Dengue virus. This virus is transmitted by Aedes sp. Many studies have been carried out on the use of plants as biological insecticides, one of which is purple eggplant (Solanum melongena L.). This study aims to determine whether Solanum melongena L. extract spray can be used as an insecticide for Aedes sp. This research was a true experimental study, with a sample of 25 Aedes sp. 2-5 days old. The treatment given was eggplant extract spray with a concentration of 80%, 60% and 40% then left for 24 hours, with 3 replications. The concentration of 80% ethanol extract caused 84% of the deaths of Aedes sp., The concentration of 60% caused 68% of deaths, and a concentration of 40% caused 44% of deaths. The p-value of the probit test was 0.000 (Solanum melongena L. ethanol extract in spray form significantly caused the death of Aedes sp.) LC50 and LC90 values were at concentrations of 49.124% and 81.343%. Spray of Solanum melongena L. ethanol extract can be used as natural insecticide for Aedes sp.